Nanocomposite Catalysts for Steam Reforming of Methane and Biofuels: Design and Performance - Sadykov, Vladislav; Mezentseva, Natalia; Alikina, Galina; Bunina, Rimma; Pelipenko, Vladimir; Lukashevich, Anton; Vostrikov, Zakhar; Rogov, Vladimir; Krieger, Tamara; Ishchenko, Arkady; Zaikovsky, Vladimir; Bobrova, Lyudmila; et al. (IntechOpen, 2011)
None